Analisis Kebijakan Luar Negeri Indonesia dalam G20 Bali Leaders Declaration - Nur Selinda (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
This study aims to analyze Indonesia’s foreign policy in the G20 Bali Leaders’ Declaration of 2022 by mapping national interests to understand the direction and priorities of Indonesian diplomacy amid complex global geopolitical dynamics. Employing a qualitative descriptive-analytical approach and the Rational Choice Theory framework, this research examines how Indonesia, as G20 Presidency, conducted rational calculations between domestic interests and external pressures—particularly regarding the Russia–Ukraine conflict. The findings reveal that Indonesia successfully embedded its national interests into four main dimensions: non-traditional security, strategic economy (energy transition, digitalization, food security), an inclusive global order, and ideological values rooted in the free and active principle. These were effectively integrated into the final declaration. Through an active-inclusive diplomatic strategy including shuttle diplomacy and carefully neutral diplomatic language Indonesia maintained consensus despite deep geopolitical polarization. This demonstrates that Indonesia’s foreign policy during its G20 Presidency was the result of deliberate rational choice, not only addressing global challenges but also reinforcing its role as a credible middle power and bridge-builder. The study contributes theoretically to rationality-based foreign policy analysis and offers practical insights for future Indonesian multilateral diplomacy.